TWENTY YEARS AFTER "ABSOLUTE CHRONOLOGY: ARCHAEOLOGICAL EUROPE 2500‐500 BC" NEW DATA ON ITALIAN PROTOHISTORY. Issue 1 (15th January 2019) - Guidi, Alessandro
ABSTRACT: The article is a tribute to the pioneering role of Klavs Randsborg in the early Nineties in search for a new comprehensive chronology for Italian and European prehistory based on a combination of dendrodates with C14 dates. The debate of the last 25 years on this matter is presented, demonstrating a scholarly split, in particular in Italy. At the same time, an Italian peculiarity, the presence of layers of volcanic eruptions mixed with archaeological deposits is proposed as a sort of meeting ground for opponents and proponents of absolute chronology and a way to pair it with known cultural phenomena.